SLAVES AS COLLATERALS, CAMPINAS - 1865-1874 - Rosa Ribeiro, Maria Alice [UNESP]; Alvim de Camargo Penteado, Maria Aparecida (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2020)
The article aims at analyzing credit based on notarial deeds on loans, pledged by public mortgage, in the county of Campinas, Province of Sao Paulo, from 1865 to 1874. The information is based on the general mortgage register - Book n. 2 - denominated 'Inscricoes de Hipotecas Especiais'. The analysis concentrates on the role of slave property as collateral in the mortgage market. We showed the composition of the collateralized slaves in terms of sex, origin and age, and the wealth and occupations of creditors and debtors.
Keywords: Slaves; mortgage; credit relations; coffee economy; Campinas